Cultural manifestation in superstition of Minangkabau society - Ridha Hasnul Ulya; Harris Effendi Thahar; Yasnur Asri; Agustina Agustina (International Conferences on Educational, Social Sciences and Technology)
This article aims to reveal philosophy level from axiology (use) of literature in the society of Minangkabau’s superstition viewed from cultural manifestation. This research is a content analysis researh using descriptive qualitative method. The research was done in 10 places in Luhak Kubuang Tigo Baleh Minangkabau namely Salayo, Cupak, Gantuang Ciri, Guguak, Koto Anau, Muara Paneh, Kota Solok, Talang, Panyangkalan, dan Kinari.The data in this research is the statements of superstition in KubuangTigoBaleh society which is obtained from observation and indepth interview withpenghulu, cerdik pandai, and alim ulama. In analyzing the data, the research usedMiles danHubeman’s modelsthrough three steps (1) data reduction, (2) data display and (3) conclusion. Based on the findings it can be concluded that There are four patterns of superstition, namely negative, positive, prediction and witchcraft pattern. Moreover, in the process of pattern meaning the lofty ethic values are framed and considered as local wisdom of the Minangkabau society, especially in KubuangTigoBaleh which is appropriate, well-mannered, educated and existence acknowledged as a belief.